Higher neural demands on stimulus processing after prolonged hospitalization can be mitigated by a cognitively stimulating environment - Marušič, Uroš (Psihološka obzorja (Ljubljana), 2021)
Prolonge d periods of complete physical inactivity or bed rest trigger various alterations in the functional and metabolic levels of the human body. However, bed rest-related adaptations of the central nervous system are less known and thoroughly studied. The aim of this study was to investigate brain electrophysiological changes using event-related potentials (ERPs) after 14 days of bed rest and 12 consecutive sessions of computerized cognitive training (CCT). Sixteen older (Mage= 60 years) healthy volunteers were randomly divided into a CCT treatment group and an active control group. All participants performed ERP measurements based on the foveal visual presentation of a circle on a black background before and after bed rest. After 14 days of bed rest, participants in the control group showed increased peak P1 amplitude (p = .012), decreased P1 latency (p = .024), and increased P2 amplitude (p = .036), while the CCT group also showed decreased P1 latency (p = .023) and decreased P2 latency (p = .049). Our results suggest that, even from a central adaptation perspective, prolonged periods of physical inactivity or bed rest trigger additional neural recruitment and should therefore be minimized, and that CCT may serve as a tool to mitigate this. Future research should focus on other aspects of central nervous system adaptation following periods of immobilization/hospitalization to improve our knowledge of infl uence of physical inactivity and its eff ects on cortical activity and to develop appropriate countermeasures to mitigate functional dysregulation.
Keywords: aging; computerized cognitive training; EEG; electroencephalography; elektroencefalografija; hospitalizacija; immobilization; imobilizacija; physical inactivity; računalniški kognitivni trening; staranje; telesna neaktivnost